Body composition of Cameroonian lactating women determined by anthropometry, bioelectrical impedance, and deuterium dilution - Medoua, Gabriel Nama; Nana, Estelle Sajo; Essa’a, Véronique J.; Ntsama, Patricia M.; Matchawe, Chelea; Rikong, Honorine Adie; Essame Oyono, Jean Louis (Nutrition (Burbank, Los Angeles County, Calif.), 2011)
This study compared body composition estimates using deuterium dilution, multiple-frequency bioelectrical impedance analysis (BIA), and skinfold thickness techniques in a group of Cameroonian lactating women. Body fat, fat-free mass, and total body water in 44 Cameroonian lactating women (2.63 ± 1.31 mo postpartum) were assessed by deuterium dilution, the Siri or black-specific derived Durnin-Womerley equation, and 12 BIA-prediction equations developed in samples of subjects of white, black, black-and-white, or unspecified racial background, respectively. Compared with deuterium dilution, anthropometry and BIA-based predictive equations overestimated body fat by 2.7 to 11.7 kg; thus, fat-free mass and total body water were underestimated. In all cases, the significant biases resulted in large 95% limits of agreement, yielding unacceptable potential bias at the level of the individual. However, the exclusion of suprailiac skinfold in the calculation, yielding to non-significant ( P < 0.05) bias, improved the prediction of body composition in Cameroonian lactating women using the Durnin-Womersley and Siri equations. It is essential to adjust the Durnin-Womersley equation before using it in the Siri equation for the prediction of body composition in lactating women. Further development and cross-validation of prediction equations from BIA specific to lactating women is needed.